Magyar–szovjet írói kompromisszum francia közvetítéssel. Orosz levéltári iratok Vercors francia író 1957 eleji moszkvai megbeszéléseiről - Seres, Attila (Acta Scientiarum Socialium, 2016)
Hungarian and Soviet Writers’ Compromise on French Intervention. Russian Archival Documents on French Writer Vercors’s Negotiations in Moscow in Early 1957. The paper presents some newly found Russian archival sources on the political activity of famous French writer Vercors (Jean Marcel Bruller 1902–1991) towards the Hungarian revolution in 1956. All sources were written in Russian language and all of them are housed in Russian archives including the former archives of the Central Committee of the Soviet Communist Party. The documents are published in Hungarian translation. Vercors was invited to Moscow before the Hungarian revolution in 1956 and he managed to travel there in February–March 1957. Taking advantage of his authority among the Soviet intelligentsia, during his negotiations in Moscow he as a French writer of Hungarian Jewish descent tried to convince some of his Soviet colleagues about the necessity of an international writer’s meeting with the participation of French, Soviet and Hungarian authors, aiming to reach a common standpoint about the Hungarian revolution.